2018
DOI: 10.4081/pr.2018.7232
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Vertebral Fractures in Pediatric and Adolescent Patients

Abstract: Spinal injuries in children and adolescents are rare injuries, but consequences for the growing skeleton can be devastating. Knowledge of accident causes, clinical symptoms and diagnostics should be part of every trauma department treating these patients. We retrospectively analyzed patients with radiographically proven vertebral fractures of the spine. After clinical examination and tentative diagnosis the fractures and injuries were proven with conventional X-ray, computed tomography (CT) scans or magnetic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 74 publications
2
30
1
3
Order By: Relevance
“…Thus, prevention and treatment of osteoporosis (such as calcium and vitamin D supplement, bisphosphonates) needs to be emphasized to help reduce the risk of traumatic spinal fractures in elderly. [19] For individuals over 15 years, slips, trips, or falls were the predominant cause. Especially in elderly population, more than half of the traumatic spinal fractures were caused by slips, trips, or falls.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, prevention and treatment of osteoporosis (such as calcium and vitamin D supplement, bisphosphonates) needs to be emphasized to help reduce the risk of traumatic spinal fractures in elderly. [19] For individuals over 15 years, slips, trips, or falls were the predominant cause. Especially in elderly population, more than half of the traumatic spinal fractures were caused by slips, trips, or falls.…”
Section: Discussionmentioning
confidence: 99%
“…In another study examining PST, neurological deficits were observed in 13 (20%) of the 20 patients (3.7% of the total cohort) requiring operative treatment [13]. It was found that 43.3% of our patients had neurological deficits and 63.3% of all patients required surgery.…”
Section: Discussionmentioning
confidence: 73%
“…Spinal injury of children are rare injury and most common courses are fall and accident. 9) In the cases of thoracolumbar fractures, traffic accident is most common course. 3) Seatbelt injuries of the adult spine have been well described and usually present as three-column injuries requiring surgical instrumentation.…”
Section: Discussionmentioning
confidence: 99%